2014
DOI: 10.1007/s10461-014-0925-6
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Syndemics are Additively Associated with Worse ART Adherence in HIV-Infected Individuals

Abstract: Adherence to antiretroviral therapy (ART) among HIV-infected individuals is necessary to both individual and public health, and psychosocial problems have independently been associated with poor adherence. To date, studies have not systematically examined the effect of multiple, co-occurring psychosocial problems (i.e., “syndemics”) on ART adherence. Participants included 333 HIV-infected individuals who completed a comprehensive baseline evaluation, as part of a clinical trial to evaluate an intervention to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
75
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 29 publications
7
75
1
1
Order By: Relevance
“…Furthermore, it is necessary to notice the important role played by the low use of substances like alcohol and drugs, which were related in a direct way with the behavioral competencies performance, this ones mediating their influence on medication-adherence behaviors. In an opposite direction to the reported on studies recently conducted around the world [23][24][25], for this sample it is evidenced a low use of both substances, whose average were 1.34 for the use of alcohol and 1.55 for the use of drugs.…”
Section: Discussioncontrasting
confidence: 96%
“…Furthermore, it is necessary to notice the important role played by the low use of substances like alcohol and drugs, which were related in a direct way with the behavioral competencies performance, this ones mediating their influence on medication-adherence behaviors. In an opposite direction to the reported on studies recently conducted around the world [23][24][25], for this sample it is evidenced a low use of both substances, whose average were 1.34 for the use of alcohol and 1.55 for the use of drugs.…”
Section: Discussioncontrasting
confidence: 96%
“…Often key populations simultaneously belong to more than one risk group (such as sex workers who inject drugs) and frequently experience syndemics, synergistically interacting co-prevalent diseases and psychosocial conditions (e.g. early childhood trauma, depression and substance use), associated with worse HIV care outcomes[35,36*,37]. Despite these challenges, evidence shows that treatment can be equally effective among MSM, sex workers, and PWID as other populations when these challenges are appropriately addressed with culturally-competent care[38,39**], such as when PWID are simultaneously provided with OST.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been many interventions developed to promote ART adherence, and these programs have often produced significant improvements in adherence; however, the magnitude of change has been relatively modest (Amico, Harman, & Johnson, 2006; Finitsis, Pellowski, & Johnson, 2014; Simoni, Amico, Pearson, & Malow, 2008). One explanation for these modest effects is that generally, traditional ART adherence interventions do not simultaneously address psychosocial problems—a crucial risk factor for non-adherence (Blashill, Bedoya, Mayer, O’Cleirigh, et al, 2015; Parsons, Rosof, & Mustanski, 2008; Gonzalez et al, 2011). Indeed, meta-analytic results have found that treating psychosocial problems (e.g., depression) improves ART adherence (Sin & DiMatteo, 2014).…”
mentioning
confidence: 99%